2015
DOI: 10.1158/2326-6066.cir-14-0159
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Blockade Immunotherapy Relies on T-bet but Not Eomes to Induce Effector Function in Tumor-Infiltrating CD8+ T Cells

Abstract: Coinhibitory receptor blockade is a promising strategy to boost T-cell immunity against a variety of human cancers. However, many patients still do not benefit from this treatment, and responders often experience immune-related toxicities. These issues highlight the need for advanced mechanistic understanding to improve patient outcomes and uncover clinically relevant biomarkers of treatment efficacy. However, the T cell-intrinsic signaling pathways engaged during checkpoint blockade treatment are not well def… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…We speculate that mTOR activation leads to the expression of T-bet in DLN CTLs stimulated by FCCP together with PD-L1 blockade. T-bet is important for the antitumor function of CTLs as well as for the development of memory precursors, which potentially give rise to the sufficient numbers of terminally differentiated effector CTLs required for tumor regression (52,53). On the other hand, terminally differentiated CTLs, which strongly express Eomes, were tolerized by chronic antigen recognition (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that mTOR activation leads to the expression of T-bet in DLN CTLs stimulated by FCCP together with PD-L1 blockade. T-bet is important for the antitumor function of CTLs as well as for the development of memory precursors, which potentially give rise to the sufficient numbers of terminally differentiated effector CTLs required for tumor regression (52,53). On the other hand, terminally differentiated CTLs, which strongly express Eomes, were tolerized by chronic antigen recognition (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a murine model of lung adenocarcinoma, T-bet deficiency led to a marked induction of tumor load (25). More recently, T-bet has been shown to be required for promoting blockade-induced CD8 þ T-cell effector responses sufficient to eradicate disseminated leukemia in an animal model (26). Furthermore, high numbers of T-bet þ intratumoral lymphoid cells have been found to correlate with improved outcome in gastric cancer (27) and in high-grade cervical intraepithelial neoplasia (28).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that treatment with combination checkpoint blockade (anti-PD-1/CTLA-4/LAG-3) prevented T-cell deletion and promoted effector cytokine production during cancer immunotherapy (21, 23). Here, treatment with IL2c resulted in more than a 5-fold increase in transferred T-cell numbers at day 8 compared to checkpoint blockade treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously identified the pro-apoptotic protein Bim (encoded by Bcl2l11 ) as necessary for T-cell deletion in Alb:Gag hosts (21, 23). Here, Bcl2l11 gene expression was observed in untreated T cells from the tolerizing environment, but was nearly undetectable following treatment with IL2c (Fig.…”
Section: Resultsmentioning
confidence: 99%